Link between the skin and autism spectrum disorder - Man, Mao-Qiang; Yang, Shuyun; Mauro, Theodora M.; Zhang, Guoqiang; Zhu, Tingting (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a common neurological disorder. Although the etiologies of ASD have been widely speculated, evidence also supports the pathogenic role of cutaneous inflammation in autism. The prevalence of ASD is higher in individuals with inflammatory dermatoses than in those without inflammatory diseases. Anti-inflammation therapy alleviates symptoms of ASD. Recent studies suggest a link between epidermal dysfunction and ASD. In murine model, mice with ASD display epidermal dysfunction, accompanied by increased expression levels of proinflammatory cytokines in both the skin and the brain. Children with ASD, which develops in early lifetime, also exhibit altered epidermal function. Interestingly, improvement in epidermal function alleviates some symptoms of ASD. This line of evidence suggests a pathogenic role of cutaneous dysfunction in ASD. Either improvement in epidermal function or effective treatment of inflammatory dermatoses can be an alternative approach in the management of ASD. We summarize here the current evidence of the association between the skin and ASD.